If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-5(5x-4)=3(2x-6)
We move all terms to the left:
3x-5(5x-4)-(3(2x-6))=0
We multiply parentheses
3x-25x-(3(2x-6))+20=0
We calculate terms in parentheses: -(3(2x-6)), so:We add all the numbers together, and all the variables
3(2x-6)
We multiply parentheses
6x-18
Back to the equation:
-(6x-18)
-22x-(6x-18)+20=0
We get rid of parentheses
-22x-6x+18+20=0
We add all the numbers together, and all the variables
-28x+38=0
We move all terms containing x to the left, all other terms to the right
-28x=-38
x=-38/-28
x=1+5/14
| 3c+45=8c+60 | | 8b+6+9b-7=180 | | 5(5a-3)=-135 | | 7x-19=5x+17 | | 10r−1=7r+26 | | -3/(x-2)=1 | | 7x-19=5x+17 7x-19=5x+17 | | 5y+2y-9=4y-y+19 | | 250-5d=400-7 | | 5.6+.4x=10 | | 24+x=-7x | | 6x+200=−6x+500 | | 65/13=35/x | | -7(-4x+4)=6(4x-4) | | 9g=5g-8 | | -10x+5=-6x=-35 | | -3/2(x+2)=21 | | 43.44=9g+3.57 | | 9/20x=180 | | 0,5x^2+5,5x=73 | | -8x+2(3+4x)=6 | | 6x-3=129 | | 5/10x+3/2=7 | | 17d=16d+19 | | -4(10+3x)-(x-8)=-9 | | x-5-5x=-9 | | 3h+9=51 | | 6x-10=-5x+89 | | 12=7x-4+x | | -6+10g=8g+10 | | -10+8z=6z | | 9+3a-4= |